Do outdoor workers know their risk of NMSC? Perceptions, beliefs and preventive behaviour among farmers, roofers and gardeners. (8th May 2017) - Zink, A.; Wurstbauer, D.; Rotter, M.; Wildner, M.; Biedermann, T.
Abstract: Background: Non‐melanoma skin cancer (NMSC) was officially recognized in 2015 as an occupational disease for outdoor workers in Germany. Together with the enormous socioeconomic impact of NMSC, this has led to the continuous demand of evidence‐based prevention. However, studies assessing the perceptions and beliefs along with risk behaviour of outdoor workers as an essential prerequisite for prevention are rare. Objective: To assess perceptions, beliefs, barriers, risk and preventive behaviours towards non‐melanoma skin cancer among different outdoor groups as a basis for the development of sustainable prevention programmes. Patients and Methods: Cross‐sectional study among outdoor workers of three different occupational groups (farmer, gardener, roofer) using a 20‐question online survey on NMSC awareness, risk and preventive behaviours. Results: Between March and April 2016, 353 outdoor workers participated in the study. Of these, 153 (43.4%) reported never to use sunscreen during work. Wearing headgear and long pants were the most common sun protection measures. Poor use of sunscreen was more likely in males and farmers. A low perceived skin cancer risk was significantly associated with poor use of sunscreen, long‐sleeved shirts, sunglasses and headgear. Conclusions: Despite great evidence on NMSC risk in outdoor professions throughout the literature, high‐risk groups in fact are not yet aware of the topic. Sustainable target group‐oriented awareness prevention programmes are needed to lower the immense burden of NMSC.